Treasure island: ladybird classics - Faraday, Joyce; Frankland, David Stevenson, Robert Louis (Ladybird Loughborough, 1994)
When Jim Hawkins sets off as a cabin boy on the "Hispaniola" he looks forward to the excitement of searching for buried treasure. But he doesn't know that spine-chilling adventure on Treasure Island awaits him and murderous struggles with Long John Silver and his cut-throat pirate band.